Social solidarity and cultural preservation: the role of female sekaa gong in Ubud - Suharta, I Wayan; In Diana Sari, Ni Luh Desi; Sadguna , I Gde Made Indra (Gelar : Jurnal Seni Budaya, 2024)
Female Sekaa Gong is a collective of women in Ubud Village who unite to perform Balinese music, transforming individual ideas into a collective vision. This group fosters social relationships and a sense of togetherness among its members. This article explores the intricacies of the Female Sekaa Gong, highlighting its role in preserving traditional Balinese music (Karawitan) and providing feminine aesthetic nuances. The research, conducted through a qualitative interpretive method within a cultural studies paradigm, examines the positionality of the Female Sekaa Gong in social and touristic contexts. Findings indicate a rise in the number of Female Sekaa Gong in Ubud Village, motivated by five key factors: religious emotion, a sense of humiliation, status improvement, actualization of beauty, and the desire to create tourist performances. The Female Sekaa Gong plays several roles in ritual and social activities, including: (1) serving as a ritual complement; (2) building social solidarity; (3) expanding traditional roles; and (4) preserving cultural values. Its presence marks a shift in the social paradigm regarding gender norms in gamelan performance, reflecting a dynamic interplay between tradition and modernity and adapting to contemporary circumstances.